Examining Two Theoretical Models Predicting American and Dutch Parents' Mediation of Adolescent Social Media Use. Issue 3 (2nd July 2016) - Krcmar, Marina; Cingel, Drew P.
ABSTRACT: The goal of the present study was to utilize two theoretical models, one based on a mediation approach and the other on the theory of planned behavior (TPB), to understand parents' mediation of their adolescents' social media use. Data were collected from parents of adolescents ages 10–18 in two countries, the United States (US) and the Netherlands. Results indicated significant differences between the two samples. Specifically, American parents reported more concern about adolescent social media use, more positive attitudes and perceived subjective norms to control adolescent use, and higher levels of active and restrictive mediation. In general, demographics and parental concern accounted for more explained variance in mediation behaviors among Dutch parents, and the TPB-based variables accounted for more explained variance among American parents. Results suggest important implications for the integration of different theoretical models to explain parent mediation behavior.